Reflecting on – traditions, ceremony, and the formation of bachelor-prepared nurses. Issue 2 (4th March 2019) - Alzghoul, Manal M.; Spadoni, Michelle
ABSTRACT: In this article, we explore the ways that the traditional nursing oath ceremony might serve as a reflective transformative moment for first-year students as they take their first tentative steps in a developmental journey of being and becoming registered nurses. Traditions in professional programs act as a rite of passage and hold the promise of an invitation and a new sense of belonging. This discussion explores the possibilities that exist within reflective transformative learning moments. The discussion unfolds through our eyes as nursing faculty teaching in an undergraduate nursing program. We recall our experience of practicing with first-year nursing students, and discuss the age-old debate: is the focus of teaching delivering content, or the formation of practitioners?